Relationship between riparian zones and water quality in the main watersheds of Ushuaia City, Tierra del Fuego (Argentina) - Granitto, María (2025)
Background Ushuaia City has experienced much population growth and still lacks secondary treatment for its wastewater. As a result, most of the discharge is directed into the lotic ecosystems that cross the urban environment. This paper assesses the relationship between riparian areas and water quality along an urbanization gradient in the city’s main watersheds: Pipo River, Buena Esperanza Stream and Arroyo Grande River. Results The Riparian Forest Quality Index adapted for Patagonia showed a positive correlation with the Fuegian Water Quality Index (r=0.83, p<0.05). Diferences in the riparian index along the urban gradient were detected in all the studied watersheds. In general, non-urbanized sites in the upper zones showed very good or good quality while urbanized sites showed worse riparian conditions. Furthermore, in relation to the Fuegian Water Quality Index, this work showed spatial and temporal variations. The Pipo River watershed showed no statistically signifcant diferences among sampling sites, although water quality decreased over time at the urbanized site near the outlet of the river (in March 2018 the Fuegian Water Quality Index was 88 and in March 2022 it was 38). In the Buena Esperanza Stream, signifcant diferences were detected among sampling sites; water quality at the non-urbanized zones in the upper section and upper-middle section was higher than at the urbanized sites. In the Arroyo Grande River, despite the lower ranges of the Fuegian Water Quality Index observed at the urban site near the outlet, no signifcant diferences were identifed between study sites. Conclusion The relationship of both indices supports the relevance of the environmental surroundings of the watercourses and how their ecological integrity afects water quality in urban lotic ecosystems. The watersheds studied here are strongly linked to the complex dynamics of a growing city which was refected by the Fuegian Water Quality. Our fndings provide a scientifc foundation for sustainable environmental management. We recommend integrated water resources management that not only ceases the direct discharge of wastewater into watercourses but also implements measures to protect and restore the riparian environment as a fundamental measure for the conservation of urban lotic ecosystems.